Commercial Fresh Market, Wine, Juice, and Jelly Grape Cultivars for Florida, [2018] - J. Breman; P. C. Andersen (EDIS)
HS-1152, a 4-page illustrated fact sheet by J. Breman and P. C. Andersen, describes the characteristics needed in cultivars for successful commercial grape production in Florida. Includes references and information on cultivars recommended by IFAS for wine, juice and jelly, and fresh market, plus fresh market muscadine cultivars for planting on a trial basis, and sensory evaluation results. Published by the UF Department of Horticultural Sciences, June 2018